Electrons Extraction from MWCNT/PEO Composites - Mohammed, Nadjima Benkara; Nor, Roslan Md; Benouattas, Noureddine (Sumy State University, 2018)
Electron field emission was investigated from multi-walled carbon nanotubes (MWCNT)/polyethylene oxide (PEO) composites with (5, 15, 25, 33, 40 and 50wt.% of MWCNTs). The resulted samples were characterized using Raman spectroscopy to estimate The MWCNTs-PEO (Nanotubes-Polymer) interaction through the shifting or width alteration of the peaks. The SEM micrographs were issued to investigate the surface morphology of the samples. In addition, and in order to gain additional understanding of the filler content and the samples thermal stability; the TGA technique was applied. The current density versus applied electric field J(E) and current stability of the prepared composites were measured using a range of voltages. Here, the 33wt.% composite displayed the lowest turn on field of 6.51V/μm, whereas the highest current density achieved was 1.17mA/cm2 by the 40wt.% composite.